Temporal hyper-precision of brainstem neurons alters spatial sensitivity of binaural auditory processing with cochlear implants - Müller, Michaela; Hu, Hongmei; Dietz, Mathias; Beiderbeck, Barbara; Ferreiro, Dardo N.; Pecka, Michael (Frontiers in Neuroscience, 2023)
The ability to localize a sound source in complex environments is essential for communication and navigation. Spatial hearing relies predominantly on the comparison of differences in the arrival time of sound between the two ears, the interaural time differences (ITDs). Hearing impairments are highly detrimental to sound localization. While cochlear implants (CIs) have been successful in restoring many crucial hearing capabilities, sound localization via ITD detection with bilateral CIs remains poor. The underlying reasons are not well understood. Neuronally, ITD sensitivity is generated by coincidence detection between excitatory and inhibitory inputs from the two ears performed by specialized brainstem neurons. Due to the lack of electrophysiological brainstem recordings during CI stimulation, it is unclear to what extent the apparent deficits are caused by the binaural comparator neurons or arise already on the input level. Here, we use a bottom-up approach to compare response features between electric and acoustic stimulation in an animal model of CI hearing. Conducting extracellular single neuron recordings in gerbils, we find severe hyper-precision and moderate hyper-entrainment of both the excitatory and inhibitory brainstem inputs to the binaural comparator neurons during electrical pulse-train stimulation. This finding establishes conclusively that the binaural processing stage must cope with highly altered input statistics during CI stimulation. To estimate the consequences of these effects on ITD sensitivity, we used a computational model of the auditory brainstem. After tuning the model parameters to match its response properties to our physiological data during either stimulation type, the model predicted that ITD sensitivity to electrical pulses is maintained even for the hyper-precise inputs. However, the model exhibits severely altered spatial sensitivity during electrical stimulation compared to acoustic: while resolution of ITDs near midline was increased, more lateralized adjacent source locations became inseparable. These results directly resemble recent findings in rodent and human CI listeners. Notably, decreasing the phase-locking precision of inputs during electrical stimulation recovered a wider range of separable ITDs. Together, our findings suggest that a central problem underlying the diminished ITD sensitivity in CI users might be the temporal hyper-precision of inputs to the binaural comparator stage induced by electrical stimulation.